Critical thinking skills: The academic ability, mastering concepts, and analytical skill of undergraduate students - Permana, Tutut Indria; Hindun, Iin; Rofi'ah, Ndzani Latifatur; Azizah, Ardiani Samti Nur (University of Muhammadiyah Malang, 2019)
Science and technology development in the 21st-century has been demanding educators to provide learning activities which stimulate students’ critical thinking skills. This study aimed to find out the correlated factors of the students’ critical thinking skills as well as of which was the strongest determinant in leveling the skills. The subject of this correlational research was 112 undergraduate students in the Department of Biology Education, Universitas Muhammadiyah Malang who took Botany course. There were four variables measured in this study, namely academic ability, mastering concepts, analytical skill, and critical thinking skills. The data of academic ability was obtained from students' cumulative index in the previous semester while the three other variables were measured using final exam test. All of the variables then analyzed using multiple linear regression. The results showed that the three predictor variables (mastering concepts, academic ability, and analytical skill) gave effective contributions toward students’ critical thinking skills, with the percentages of 3.84%, 32.25%, and 54.26% respectively. Therefore, the results of this study could be a basic reference in designing learning process which empower the students’ critical thinking skills.